2020
DOI: 10.1523/jneurosci.0874-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the Direct Reciprocal Hippocampal-Anterior Thalamic Pathways for Spatial Learning

Abstract: The hippocampus is essential for normal memory but does not act in isolation. The anterior thalamic nuclei may represent one vital partner. Using DREADDs, the behavioral consequences of transiently disrupting anterior thalamic function was examined, followed by inactivation of the dorsal subiculum. Next, the anterograde transport of an adenoassociated virus expressing DREADDs was paired with localized intracerebral infusions of a ligand to target specific input pathways. In this way, the direct projections bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 79 publications
4
34
0
Order By: Relevance
“…In contrast, inactivation of the distal SUB, but not the proximal SUB containing NAC-p neurons, has been shown to impair spatial working memory in a Morris water maze task (23). In addition, Nelson et al (67) found that the reciprocal connection between the SUB and anterior thalamic nuclei, including the AV, is required for a modified T-maze task, in which animals could not use intramaze cues. Collectively, while multiple SUB projections are recruited in spatial working memory tasks, their necessity appears to depend on various factors, including the type of behavioral task, task difficulty, delay length, and richness of available cues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inactivation of the distal SUB, but not the proximal SUB containing NAC-p neurons, has been shown to impair spatial working memory in a Morris water maze task (23). In addition, Nelson et al (67) found that the reciprocal connection between the SUB and anterior thalamic nuclei, including the AV, is required for a modified T-maze task, in which animals could not use intramaze cues. Collectively, while multiple SUB projections are recruited in spatial working memory tasks, their necessity appears to depend on various factors, including the type of behavioral task, task difficulty, delay length, and richness of available cues.…”
Section: Discussionmentioning
confidence: 99%
“…This network model suggests that the ATN are key structures within both diencephalic and temporal lobe memory systems ( Aggleton and Brown, 1999 ; Ranganath and Ritchey, 2012 ). In rodents, for instance, anterior thalamic lesions severely impair spatial learning, mirroring hippocampal damage ( Morris et al, 1982 ; Warburton and Aggleton, 1999 ; Moran and Dalrymple-Alford, 2003 ); moreover, disconnection studies suggest that the hippocampal formation and ATN are functionally interdependent ( Sutherland and Rodriguez, 1989 ; Shibata, 1993 ; Nelson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With dense and reciprocal connections with the hippocampus [13e15], and its involvement in cognitive function [15e17], the anterior nucleus of thalamus (ANT) has been suggested as an extended hippocampal system [18e20]. A rodent study found that disrupting information flow between the hippocampal and ANT impaired spatial working memory performance [21]. Electrical stimulation directly targeted to the hippocampus can disrupt memory performance [22,23].…”
Section: Introductionmentioning
confidence: 99%